Предмет: Математика,
автор: datuashvilidavid
Помогите пожалуйста. Упростить 12х-3-(4х-1)
Ответы
Автор ответа:
0
Ответ:
12х-3-4х+1=(12х-4х)+(-3+1)=8х-2
Автор ответа:
0
Ответ:
2 (4х-1)
8х-2
Пошаговое объяснение:
12х-3-(4х-1)
-(4х-1)=1-4х
12х-3+1-4х
12х-3+1-4х=(12х-4х)+(1-3)
(12х-4х)+(1-3)
12х-4х=8х
8х+(1-3)
-3+1=-2
8х + -2
8х-2
2(-1+4х)
Похожие вопросы
Предмет: Другие предметы,
автор: thappiest
Предмет: Русский язык,
автор: амадина54
Предмет: Английский язык,
автор: GZHILKINA
Предмет: Английский язык,
автор: Юля2718
Предмет: Английский язык,
автор: KarinkaMandarinka222